Theoretical investigations on the interactions of glucokinase regulatory protein with fructose phosphates. (February 2016) - Ling, Baoping; Yan, Xueyuan; Sun, Min; Bi, Siwei
Graphical abstract: Highlights: F1P and F6P can bind to the same active site with different binding mode. Ligands affect the conformational spaces and motions of GKRP. Electrostatic interaction provides a major driving force for the ligand binding. F6P makes loop2 of GKRP more protruding and strengthens its contacts with GK. The residues 179-184 play a critical role in the binding of phosphate group. Abstract: Glucokinase (GK) plays a critical role in maintaining glucose homeostasis in the human liver and pancreas. In the liver, the activity of GK is modulated by the glucokinase regulatory protein (GKRP) which functions as a competitive inhibitor of glucose to bind to GK. Moreover, the inhibitory intensity of GKRP–GK is suppressed by fructose 1-phosphate (F1P), and reinforced by fructose 6-phosphate (F6P). Here, we employed a series of computational techniques to explore the interactions of fructose phosphates with GKRP. Calculation results reveal that F1P and F6P can bind to the same active site of GKRP with different binding modes, and electrostatic interaction provides a major driving force for the ligand binding. The presence of fructose phosphate severely influences the motions of protein and the conformational space, and the structural change of sugar phosphate influences its interactions with GKRP, leading to a large conformational rearrangement of loop2 in the SIS2 domain. In particular, the binding of F6P to GKRP facilitates the protruding loop2 contacting with GK to form the stable GK–GKRP complex. The conserved residues 179–184 of GKRP play a major role in the binding of phosphate group and maintaining the stability of GKRP. These results may provide deep insight into the regulatory mechanism of GKRP to the activity of GK.